GIVEN :
a = 1/√10 ( 3i + k) and
b = 1/7 ( 2i + 3j - 6k)
TO FIND :
( 2a- b) . [ ( a x b ) x ( a + 2b)]
SOLUTION :
◆Going with the equation given,
( 2a - b) . [ ( a x b ) x ( a + 2b)]
= (2a - b) [( a×b×a) + 2(a×b)×b]
◆BAC - CAB RULE,
A×B×C = B( A.B ) - C(A.B )
= (2a- b ) [ (b (a.a ) - a (a.b ) + 2b ( a.b) -2b (a.b]
Solving further
= (2a - b )(b - 2a)
= -4a.a -b.b
=-5.
Answer:
( 2 - b) . [ ( a x b ) x ( a + 2b)] = -5
Hoped I helped
is this for the test on schoolobjects?
Answer:
9
Step-by-step explanation:
The height is 4 feet. You calculate the area by length times height. So what multiplied by 15 is 60? Well, 15ft x 4ft = 60ft^2